The Inter-American Responses during COVID-19: Development of Green Human Rights in Indigenous Cases at the Regional and National Levels: Development of Green Human Rights in Indigenous Cases at the Regional and National Levels - Tigre, Maria Antonia; Kasznar, Alice; Harrington, Alexandra; Urzola, Natalia; Bernal, Astrid; Evans, Hayley; Van Der Kleyn, Amy (Revista de Derecho Ambiental, 2021)
Latin America is often considered the world’s most unequal region. This inequality is not limited to socioeconomic differences; it is also seen through discrepancies in access to nature, land, and natural resources. The Covid-19 pandemic has intensified existing vulnerabilities felt by communities, especially susceptible to environmental degradation through furthering their socioeconomic disadvantage. Faced with challenges related to the national implementation of certain rule of law concepts and practices, and the lack of access to sufficient domestic remedies, regional plaintiffs have often reached out to the Inter-American system as an arbiter for human rights abuses. Recent jurisprudence of both the Inter-American Court of Human Rights and the Inter-American Commission on Human Rights has broadened the scope of recognized rights infringed by State Parties to the Inter-American human rights system, particularly in fields relating to environmental issues, natural resource rights and the rights of vulnerable and marginalized communities. Critical to this is the Inter-American Court’s development of the inter-dependence of green human rights in Indigenous cases. Set against this backdrop, the Covid-19 pandemic provides an opportunity to analyze existing and evolving legal trends, giving the Inter-American human rights system fertile ground to address emerging legal topics on human rights and the environment. This article addresses this evolving jurisprudence, using recent cases brought to the Commission’s attention as case studies on the development of this relationship.